Unruly waters : how rains, rivers, coasts and seas have shaped Asia's history - Amrith, Sunni (Penguin Books, 2018)
"Asia's history has been shaped by her waters. In Unruly Waters, historian Sunil Amrith reimagines Asia's history through the stories of its rains, rivers, coasts, and seas--and of the weather-watchers and engineers, mapmakers and farmers who have sought to control them. Looking out from India, he shows how dreams and fears of water shaped visions of political independence and economic development, provoked efforts to reshape nature through dams and pumps, and unleashed powerful tensions within and between nations. Today, Asian nations are racing to construct hundreds of dams in the Himalayas, with dire environmental impacts; hundreds of millions crowd into coastal cities threatened by cyclones and storm surges. In an age of climate change, Unruly Waters is essential reading for anyone seeking to understand Asia's past and its future." -- Amazon.com.